2019
DOI: 10.3390/ma12040601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Terpyridine-Terminated Amphiphilic Block Copolymers and Their Self-Assembly into Metallo-Polymer Nanovesicles

Abstract: Polystyrene-b-polyethylene glycol (PS-b-PEG) amphiphilic block copolymers featuring a terminal tridentate N,N,N-ligand (terpyridine) were synthesized for the first time through an efficient route. In this approach, telechelic chain-end modified polystyrenes were produced via reversible addition-fragmentation chain-transfer (RAFT) polymerization by using terpyridine trithiocarbonate as the chain-transfer agent, after which the hydrophilic polyethylene glycol (PEG) block was incorporated into the hydrophobic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Their stability is also a limiting factor because their lipid building blocks are insoluble in water [ 15 , 16 ]. These limitations have prompted research into other vesicles for drug delivery, such as polymersomes from amphiphilic polymers [ 17 ], dendrimersomes from dendrimers [ 18 , 19 ], and peptosomes from self-assembling peptides [ 20 ]. However, these vehicles still have limitations due to their structural stability, low entrapment, membrane thickness, and area density, which is greatly affected by block length and the size of the polymer, dendrimers, or peptides [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their stability is also a limiting factor because their lipid building blocks are insoluble in water [ 15 , 16 ]. These limitations have prompted research into other vesicles for drug delivery, such as polymersomes from amphiphilic polymers [ 17 ], dendrimersomes from dendrimers [ 18 , 19 ], and peptosomes from self-assembling peptides [ 20 ]. However, these vehicles still have limitations due to their structural stability, low entrapment, membrane thickness, and area density, which is greatly affected by block length and the size of the polymer, dendrimers, or peptides [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10] Many studies on amphiphilic copolymers have focused on the synthesis and systematic study of their rheology in water solution. 7,8,[11][12][13][14][15] It is important to point out that the formation of micellar aggregates in water is a typical behavior of amphiphilic block copolymers, where the architecture and the length of the hydrophilic and hydrophobic blocks influence the final morphology and properties. 2,8,10,[16][17][18] For example, Colombani et al reported the synthesis and study of poly(n-butyl acrylate)-block-poly(acrylic acid) diblock copolymers prepared via ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…In order to incorporate tpy motifs into a wide variety of well-defined polymers, the tpy-modified chain-transfer agents or initiators have been feasibly utilized in controlled polymerizations, such as reversible addition-fragmentation chain transfer (RAFT) [20][21][22], nitroxide-mediated radical polymerization (NMP) [23][24][25][26], and ring-opening polymerization (ROP) [27][28][29]. However, since the 2 of 9 atom transfer radical polymerization (ATRP) is often mediated by copper catalysts, the presence of uncomplexed tpy ligands could adversely affect the copper catalyst during the ATRP reaction [30,31].…”
Section: Introductionmentioning
confidence: 99%